Woman-centered Brazilian cinema filmmakers and protagonists of the twenty-first century - Draper, Jack A., III, 1976-; Rego, Cacilda (Albany : SUNY Press, 2022)
Woman-Centered Brazilian Cinema highlights the bold, inspiring, and diverse work of female filmmakers--including directors, screenwriters, and producers--and female protagonists in the twenty-first-century Brazilian film industry. This volume examines the diverse production and distribution spaces these filmmakers are working in, including documentary, experimental, and short filmmaking, as well as commercial feature films. An intersectional approach runs throughout the chapters with complex considerations around gender, race, sexuality, and class. The book features a mix of research methods and genres, with macro-level political, economic, and industry-wide views of gender disparities appearing alongside in-depth conversations with contemporary filmmakers Maria Augusta Ramos, Petra Costa, Mari Corrêa, and Paula Sacchetta, focused on micro-level personal experiences. In bringing together original essays and interviews, the volume provides valuable information for students of Brazil in general and of Brazilian film in particular.
Front Matter -- Contents -- Introduction -- Breaking Ground/Making Space in the Industry -- Recognizing Women's Contributions to Brazilian Cinema -- Behind the Scenes -- Resistance and Online Activism -- Interview with Maria Augusta Ramos -- Politics of Public/Private Spaces -- From Tweets to the Streets -- Motherhood and Making Kin in Contemporary Brazilian Cinema -- The Many Mirrors of Maria Augusta Ramos -- Interview with Petra Costa -- Intersecting Identities -- Conditions for a Twenty-First-Century Black Woman Cinema in Brazil -- Afro-Brazilian Women Creative Workers Speak -- Interview with Mari Corrêa -- Interview with Paula Sacchetta -- Contributors -- Index
JSTOR
Keywords: Women in the motion picture industry -- Brazil; Women in motion pictures; Motion pictures -- Brazil -- History; Femmes dans l'industrie cinématographique -- Brésil.; Femmes au cinéma.; Cinéma -- Brésil -- Histoire; PERFORMING ARTS / Film & Video / History & Criticism; PERFORMING ARTS / Film / History & Criticism; Motion pictures; Women in motion pictures; Women in the motion picture industry; Brazil; History